A psicoeducação em esquizofrenia e a música popular - Marques Filho, Altino Bessa (2012)
Schizophrenia is chatacterized by a combination of positive, negative, cognitive, affective, and motor symptoms, being a chronic and recurrent disorder, with incomplete remissions, different intensities of functional impairments, social awkwardness, comorbid substance abuse, reduced longevity, insufficient self-criticism and lack of support. Living together with relatives increases family burden physically and emotionally. Objectives - To evaluate and discuss aspects of psychoeducation; check whether and how schizophrenia is quoted in the Brazilian songbook and whether musical letters with illustrative drawings may be useful in psychoeducational programs. Material and Methods - a literature search was carried out using keywords psychoeducation and schizophrenia, selecting articles published in English, Spanish and Portuguese, with no date restriction, including 87 original articles with the main objective of psychoeducation in schizophrenia, published between 1987 and September 2011. In addition, Brazilian discography was evaluated in order to select songs that describe or mention signs and symptoms of schizophrenia according to DSM-IV-TR. Additionally, lyrics and melody of a music and an U.S. song was adapted into Portuguese by the author, both according to DSM-IV-TR for schizophrenia. In this case, relatives of mental patients answered the same questionnaire, before and after audio-visual presentation regarding the symptoms of schizophrenia. Data were analyzed statistically, with a significance level of p < 0,05. Results - Schizophrenia entails difficult interpersonal interaction, is stigmatized, burdens the family that needs more support to minimize the emotion expressed. The best treatment results come from the combination of medication and psychosocial techniques, including psychoeducation, both in meetings and individually. It was selected excerpts of twelve songs that best represent characteristic symptoms in isolation: delusions, hallucinations and disorganized speech; and combined: inadequacy of affection and murder; delusions and disorganized speech; delusion and hallucination; volition ambivalence, delusion, disorganized speech and suicide; hallucination and disorganized speech; and grossly disorganized behavior and attempted murder. Musical composition and adaptation to Portuguese of an American song, with didactic intension by the author, presented evidence of symptoms in schizophrenia like auditory hallucinations, commenting in dialogue activities of the self, catatonia, delusion of influence, mystical delusion and ambivalence, disorganized behavior and abulia. There was an increase in knowledge by family members about the way the person with schizophrenia thinks and perceives the facts (63.6% to 83.6%, p = 0.02), self reference (64.8% to 83.6%, p = 0.030), and possibility of feeling constantly watched (63.6% to 80.0%, p = 0.016). Conclusions – There is a structured body of theory and several reports of satisfactory experiences of psychoeducation in the treatment of schizophrenia. However, it is little used outside of major university centers, creating the need for large studies, including several artistic fields, aiming at universalization of psychoeducational programs in schizophrenia. Brazilian lyrics exemplify important aspects of schizophrenia and may be useful in this disorder psychoeducation of patients and their families, increasing motivation for treatment. Musical compositions created with didactic intention, describing aspects related to schizophrenia, may help to increase understanding of symptoms associated with mental disorders. Lyrics should be further explored as a means of psychoeducation.